Estudio de prefactibilidad para la instalación de una planta procesadora de snacks a base de maíz chulpi (Zea mays) para microondas - Godoy Altamirano, Carlos Alexander (2022)
The present research work consists of a pre-feasibility study for the installation of a process factory of snacks based on Chulpi Corn for microwave. This project will seek to answer the following question: Is it feasible to install a process factory that produces snacks based on Chulpi Corn for microwave in the market of Metropolitan Lima? First of all, the determination of the demand was carried out with the use of historical databases which were forecasted since 2022 until 2026, obtaining the projected FDD. On these data, the respective segmentation factors and the results of the survey were applied, with which a demand of 3 138 202 units was obtained for the firs yeaer. Secondly, the possible location of the process factory was analyzed considering different factors, resulting that Lurin being the optimal location for this project, by collecting data mainly from institutional pages from different regions. Thirdly, the size of the project was determined and the calculation of other relevant aspects were carried out, such as the break-even point, market, availability of raw materials and technology. Also, the size chosen was size-market relationship with a project demand of 3 285 165 units for year 5 of the project. Fourthly, the important aspects of the product were established, such as the quality, design and regulatory frameworks for it. Once obtained, the production process was determined with the use of papers from different institutions. In addition, the project carried out the quality plan, maintenance, environmental impact studies, occupational health and safety, supply chain and the plan of the process factory Finally, the total investment, costs and operating expenses were determined, making the budgeted statement of income and the financial flows, in this way, it was possible to calculate the financial, economic and social indicators that reflects the viability of the project.